An Application of Finished Test Piece Methods for Evaluating the Performance of Computer Numerical Control Machining and Turning Centers - Supakumnerd, Kittichote; Chungchoo, Chatchapol (Agriculture and Natural Resources, 2015)
Currently, many mechanical parts are produced from computer numerical control (CNC) machines including CNC machining centers and CNC turning centers. In order to keep production costs as low as possible, workpieces have to be rejected at the minimum rate. This can be done, but it depends on many parameters. One important parameter is adequate machine performance to produce the workpiece. In this research, a new technique was introduced to evaluate the performance of both CNC machining and turning centers. The first benefit of this technique is that manufacturers can evaluate a machine’s performance themselves (no expert is required). The second benefit is that the approximate workpiece dimensions can be predicted in advance. In addition, using the standard test piece, experimental results confirmed that this new technique can be used in industry.